The clinical effectiveness of static resting splints in early rheumatoid arthritis: a randomized controlled trial. - Adams, J; Burridge, J; Mullee, M; Hammond, A; Cooper, C (2008)
OBJECTIVE: To evaluate the effectiveness of static resting splints in early RA. METHODS: A multicentre, randomized, trial was conducted. Patients (n = 120) received either static resting splints [positioned with the wrist in neutral, MCP joint (MCPJ) and IP joint (IPJ) in a maximum of 60 degrees and 30 degrees of flexion, respectively] plus standardized occupational therapy or standardized occupational therapy alone. Change in grip strength (Ns), structural impairment (MCPJ ulnar deviation), applied dexterity (Button Board), self-report hand ability [Michigan Hand Outcomes Questionnaire (MHQ)], hand pain and morning hand stiffness were assessed at 0 and 12 months. RESULTS: Data for 56 (97%) splinted and 60 (97%) control group patients were analysed. Splint wear adherence was moderate; 24.5% 'never wore' the splints. The adjusted mean difference between groups for handgrip was -14.2 Ns (P = 0.342; 95% CI -43.7, 5.4); MCPJ ulnar deviation -1.1 degrees (P = 0.657; 95% CI = -6.2, 3.9); dexterity 0.1 s (P = 0.975; 95% CI = -6.6, 6.8) and self-report ability -3.0 on the MHQ score (P = 0.426; 95% CI -10.5, 4.5). Pain scores were unchanged in either group (P = 0.15). The occurrence of morning hand stiffness was reduced in a small group of splinted patients (P = 0.021), but the duration shortened in control patients (P = 0.010). CONCLUSIONS: There was no significant difference between the two interventions on grip strength, deformity, hand function and pain. The data favoured the control group and this study suggests that resting splints should not be used as a routine treatment of patients with early RA.